Effects of Fibrin Clot Inhibitors and Statins on the Intravesical Bacille Calmette–Guérin Therapy for Bladder Cancer: A Systematic Review and Meta-Analysis - Cai, Zhiyong; Hu, Jiao; Othmane, Belaydi; Li, Huihuang; Qiu, Dongxu; Yi, Zhenglin; Chen, Jinbo; Zu, Xiongbing (Frontiers in Oncology, 2021)
Abstract Objective: To assess the effect of fibrin clot inhibitors (aspirin, clopidogrel and warfarin) and statins on intravesical BCG therapy. Method: A systematic literature search was carried out through PubMed, Embase, and the Cochrane Central Search Library in March 2020. Accumulative analyses of odds ratios (ORs), hazard ratio (HR) and corresponding 95% confidence intervals (CIs) were performed. All analyses were performed by using Review Manager software version 5.3 and Stata 15.1. Results: Four cohort studies and nine case-control studies containing 3451 patients were included. The pooled analysis indicated that statins (HR=1.00; 95%CI, 0.82 to 1.22; p=1.00) and fibrin clot inhibitors (HR=1.01; 95%CI, 0.64 to 1.59; p=0.98) didn’t affect the efficacy of BCG on recurrence-free survival. The cumulative analysis showed that statins (HR=0.79; 95%CI, 0.41 to 1.49; p=0.46) and fibrin clot inhibitors (HR=1.62; 95%CI, 0.90 to 2.91; p=0.11) didn’t affect the efficacy of BCG on progression-free survival. There were no differences on cancer-specific survival (HR=1.68; 95%CI, 0.64 to 4.40; p=0.29) and overall survival (HR=1.13; 95%CI, 0.73 to 1.78; p=0.58) after taking statins. Conclusion: The present study shows that the application of fibrin clot inhibitors and statins don’t influence the efficacy of BCG on oncological prognosis. Consequently, we do not need to stop use them or change to other drugs during intravesical BCG treatment. However, large-scale multi-center prospective research is still needed to confirm the above conclusions.